Evolution of the grain size distribution in Milky Way-like galaxies in post-processed IllustrisTNG simulations - Huang, Yu-Hsiu; Hirashita, Hiroyuki; Hsu, Yun-Hsin; Lin, Yen-Ting; Nelson, Dylan; Cooper, Andrew P (Monthly notices of the Royal Astronomical Society, 2021)
We model dust evolution in Milky Way-like galaxies by post-processing the IllustrisTNG cosmological hydrodynamical simulations in order to predict dust-to-gas ratios and grain size distributions. We treat grain-size-dependent dust growth and destruction processes using a 64-bin discrete grain size evolution model without spatially resolving each galaxy. Our model broadly reproduces the observed dust-metallicity scaling relation in nearby galaxies. The grain size distribution is dominated by large grains at z ≳ 3 and the small-grain abundance rapidly increases by shattering and accretion (dust growth) at z ≲ 2. The grain size distribution approaches the so-called MRN distribution at z ∼ 1, but a suppression of large-grain abundances occurs at z < 1. Based on the computed grain size distributions and grain compositions, we also calculate the evolution of the extinction curve for each Milky Way analogue. Extinction curves are initially flat at z > 2, and become consistent with the Milky Way extinction curve at z ≲ 1 at $1/\lambda \lt 6~\rm{\mu m}^{-1}$. However, typical extinction curves predicted by our model have a steeper slope at short wavelengths than is observed in the Milky Way. This is due to the low-redshift decline of gas-phase metallicity and the dense gas fraction in our TNG Milky Way analogues that suppresses the formation of large grains through coagulation.
Published: 27 November 2020
Gesehen am 02.03.2021